Pengembangan e-LKPD Berbasis Project Based Learning Berbantuan GeoGebra Materi Transformasi Geometri pada Siswa Kelas IX - Annisa Dora Salsabila (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study presented the development of a GeoGebra-assisted electronic student worksheet (E-LKPD) based on Project Based Learning (PjBL) for transformation geometry material for ninth-grade junior high school students. The purpose of this development research was to determine the validity, practicality, and effectiveness of the developed E-LKPD. This research employed a Research and Development approach using the ADDIE model, which consisted of the stages of analysis, design, development, implementation, and evaluation. The subjects of this study were ninth-grade students of SMP Negeri 3 Bondowoso. The research instruments included validation sheets, student response questionnaires, teacher response questionnaires, interview guidelines, and learning achievement tests in the form of pre-tests and post-tests. The results showed that the developed E-LKPD met the validity criteria with an average validation score of 3.88. In terms of practicality, the E-LKPD was categorized as very practical, with an average percentage of 96.21%. Furthermore, the effectiveness test results indicated a significant improvement in students’ learning outcomes, as shown by the increase in the average pre-test score from 38.3 to a post-test score of 83.4, with an N-Gain value of 0.7, which fell into the moderate category. These findings indicated that the GeoGebraassisted PjBL-based E-LKPD was valid, practical, and effective in improving students’ understanding of transformation geometry material.
Reupload file repository 25mei 2026_Firli_Tata :: Finalisasi Repositori File 25 Mei 2026_Kurnadi
Keywords: E-LKPD; Project Based Learning; GeoGebra; transformation geometry; ADDIE